Relationship between adverse childhood experiences and resilience in college students in China - Chen, Yafan (Journal of family violence, 2023)
A great body of literature has documented that adverse childhood experiences (ACEs) are related to individuals’ psychological functioning and mental health. However, the majority of ACE studies focus on psychological dysfunction and less is known about how ACEs are associated with other positive psychological outcomes, including resilience. The current study assessed the relationship between ACEs and resilience, using a sample of college students in China. We hypothesized that college students who had ACEs would have lower levels of resilience. Data came from 1,871 college students from twelve colleges in China through an anonymous online survey between late September and early October 2020. Linear regression analyses were conducted. Aligned with our hypotheses, ACEs had a negative association with individuals’ resilience. Despite several limitations, this study found a negative association between ACEs and college students’ resilience. Preventive services and interventions are in need to protect individuals from ACEs.